Clinical Study of Incidence and Risk Factors for Abdominal Surgical Site Infections - Pradhan, Krunal; E. Shah, Riddhi; Donda, Jaykumar (Journal of Neonatal Surgery, 2025)
Background: Surgical site infections (SSIs) create substantial patient complications and death rates in diverse healthcare systems worldwide while adversely affecting surgical treatment results. SSIs present a high risk for abdominal surgery patients due to complex surgical operations and gastrointestinal tract contamination along with individual patient medical conditions. Healthcare professionals need to understand both the rate of SSIs and associated risk elements for abdominal surgeries to develop preventive measures. Methods: This prospective clinical study was conducted on patients undergoing abdominal surgical procedures at a tertiary care center. Patient demographics, preoperative variables, and intraoperative factors were recorded. Postoperative follow-up included clinical examination and laboratory investigations to detect SSIs. Data analysis encompassed descriptive statistics to ascertain the incidence of SSIs and inferential tests to know and evaluate risk factors. Results: The study analyzed 300 patients who developed postoperative SSIs among 48 of them (16%). Medical personnel isolated Staphylococcus aureus as the most frequently observed organism in their samples. Older than 60 years of age together with diabetes mellitus patients undergoing surgeries longer than expected duration at contaminated surgical sites and failing to maintain proper blood sugar levels led to higher incidence of SSI. Statistical analysis of multiple factors indicated diabetes and operations lasting longer than average that continued to demonstrate a significant risk pattern. Conclusion: The present study highlights that SSIs remain a frequent complication following abdominal surgeries. Diabetes mellitus, advanced age, and prolonged procedures notably predisposed patients to infection. The combination of well designed interventions that control blood sugar levels while improving surgical procedures shows potential to decrease the occurrence of SSIs in abdominal surgeries.